2020
DOI: 10.5267/j.ijdns.2019.9.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of machine learning algorithms for the automatic programming of computer numerical control machine

Abstract: The computer numerical control (CNC) machines are chiefly used for the production of jobs with high accuracy and high speed. The CNC machining centers perform the machining operations according to the given program instructions which are commonly programmed by a CNC programmer. In this paper, a procedure to develop an automatic CNC program for machining of different types of holes by using different machine learning algorithms is developed. The machine learning algorithms namely support vector machine (SVM) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Collect data from the risk factors of dynamic disorders reported in the study, process the pre collected data, and collect standardized datasets, which are proportionally divided into training and testing groups (Bird and Dale 2022). The training team conducted research using automatic learning algorithms to optimize the reuse pattern to obtain the best model, which can also be incorporated into damage prediction and recognition (Sharma et al 2020). The literature indicates that the biomechanical analysis methods of human joints mainly involve pressure sensitive film method and staining method, but the distribution of KOA patients needs to be analyzed through surface measurement, which is very difficult to obtain joints (Mishra et al 2022).…”
Section: Related Workmentioning
confidence: 99%
“…Collect data from the risk factors of dynamic disorders reported in the study, process the pre collected data, and collect standardized datasets, which are proportionally divided into training and testing groups (Bird and Dale 2022). The training team conducted research using automatic learning algorithms to optimize the reuse pattern to obtain the best model, which can also be incorporated into damage prediction and recognition (Sharma et al 2020). The literature indicates that the biomechanical analysis methods of human joints mainly involve pressure sensitive film method and staining method, but the distribution of KOA patients needs to be analyzed through surface measurement, which is very difficult to obtain joints (Mishra et al 2022).…”
Section: Related Workmentioning
confidence: 99%
“…Using existing data to predict the performance parameters can not only expand the space of material data but also provide guidance for material experiments and applications. Different machine learning algorithms have different sensitivities to material data in different ranges of data sets, so it is necessary to make a feature selection on specific material data samples to evaluate algorithm by performance evaluation [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…She found that axial misalignment of openings machined with high-speed steel drills depended on/was caused by tool advance and its rotational frequency. Sharma, Chawla, and Ram describe machine learning algorithms, namely support vector machine (SVM), restricted Boltzmann machine (RBM), and deep belief network (DBN), for the automatic programming of a computer numerical control machine [ 11 ]. Yusup et al estimated optimal abrasive waterjet machining control parameters using artificial bee colony [ 12 ].…”
Section: Introductionmentioning
confidence: 99%